2017
DOI: 10.1021/acs.jafc.6b05127
|View full text |Cite|
|
Sign up to set email alerts
|

Leaching of Diuron, Hexazinone, and Sulfometuron-methyl Applied Alone and in Mixture in Soils with Contrasting Textures

Abstract: When herbicides are applied in mixture, interactions among them could potentially promote changes in herbicide behavior in the soil. Thus, application mode (isolated or in mixture) and soil texture (sandy or clayey) were investigated in the total leaching of the commercial mixture diuron + hexazinone + sulfometuron-methyl, and of each isolated compound. Experiments in soil columns also evaluated the movement of each herbicide and mixtures across soil layers. In the sandy soil, the greatest total leaching was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Studies have indicated that expansive clay minerals act as excellent natural adsorbents in sediments due to their active structural sites, such as exchangeable cations, hydrophobic surfaces, and Si-OH [ 29 ]. Other studies have reported that the isolated application of the analytical standard diuron remained most concentrated in the top 15 cm of both sandy and clayey soil depths [ 30 , 31 ], which is consistent with our findings.…”
Section: Resultssupporting
confidence: 93%
“…Studies have indicated that expansive clay minerals act as excellent natural adsorbents in sediments due to their active structural sites, such as exchangeable cations, hydrophobic surfaces, and Si-OH [ 29 ]. Other studies have reported that the isolated application of the analytical standard diuron remained most concentrated in the top 15 cm of both sandy and clayey soil depths [ 30 , 31 ], which is consistent with our findings.…”
Section: Resultssupporting
confidence: 93%
“…DUR is considered weakly to moderately mobile, being strongly retained in the topsoil but less retained in deeper regions. Dos Reis et al (2017) reported that 96.1% of DUR remained in the 0-5-cm soil layer after a rainfall simulation, whereas only 0.91% remained in the 5-10-cm soil layer, confirming its low mobility through the soil profile. DUR mobility is related to soil organic carbon content and soil texture (Landry et al, 2006).…”
Section: Environmental Occurrence and Toxicity Environmental Occurrencementioning
confidence: 94%
“…Also, the combination of pesticides influences their impact on their leaching, adsorption, sorption, and desorption in the soil. Regarding this, in Brazil Dos Reis et al (2017) documented that the mixture of the herbicides sulfometuron methyl, Diuron and Hexazinone could promote changes in their respective behavior in the soil; in addition, they observed that Diuron has low mobility in the soil, since it remained in the upper layer, while Hexazinone leached heavily at deeper profiles.…”
Section: Pesticides and Their Impact On The Soil Ecosystemmentioning
confidence: 99%